Admissibility and common belief - Geir B. Asheim; Martin Dufwenberg (University of Oslo, Department of Economics, 2000)
The concept of `fully permissible sets' is defined by an algorithm that eliminates strategy subsets. It is characterized as choice sets when there is common certain belief of the event that each player prefer one strategy to another if and only if the former weakly dominates the latter on the set of all opponent strategies or on the union of the choice sets that are deemed possible for the opponent. The concept refines the Dekel-Fudenberg procedure and captures aspects of forward induction.
Keywords: C72; 330; Spieltheorie; Theorie